2017
DOI: 10.1111/tri.12925
|View full text |Cite
|
Sign up to set email alerts
|

Mineral adaptations following kidney transplantation

Abstract: Klotho is predominantly expressed in the kidney and reported to have antioxidant and antifibrotic properties. Soluble Klotho (sKl), the circulating protein cleaved from membrane-bound Klotho, is reduced significantly with kidney disease and inversely associated with mortality. sKl has not been thoroughly evaluated prospectively after kidney transplantation. Incident kidney transplant recipients (KTRs) were prospectively evaluated pretransplantation, 1, 12 and 52 weeks post-transplantation. Basic biochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…There is good evidence from clinical and experimental studies that both acute and chronic renal failure are associated with reduced expression of Klotho in the kidney, and with reduced sKlotho levels in the blood [ 43 ▪▪ , 44 47 ]. In agreement with these data, kidney transplantation in CKD patients results in a rapid rise in circulating sKlotho, and a decline in circulating FGF23 levels [ 48 ▪ , 49 ▪ ]. Conversely, treatment of mice with sKlotho improves outcome in acute and chronic renal injury models [ 50 ▪▪ ].…”
Section: Pathophysiological Role Of Klotho In Acute and Chronic Renalmentioning
confidence: 54%
“…There is good evidence from clinical and experimental studies that both acute and chronic renal failure are associated with reduced expression of Klotho in the kidney, and with reduced sKlotho levels in the blood [ 43 ▪▪ , 44 47 ]. In agreement with these data, kidney transplantation in CKD patients results in a rapid rise in circulating sKlotho, and a decline in circulating FGF23 levels [ 48 ▪ , 49 ▪ ]. Conversely, treatment of mice with sKlotho improves outcome in acute and chronic renal injury models [ 50 ▪▪ ].…”
Section: Pathophysiological Role Of Klotho In Acute and Chronic Renalmentioning
confidence: 54%
“…On the other hand, in a study covering pretransplantation and posttransplantation periods, it was found that sKlotho levels declined at 1w following transplantation and started increasing gradually afterward. At 12 w it exceeded the pretransplant level and at 52 w it was still increasing [23].…”
Section: Discussionmentioning
confidence: 90%
“…Eighteen of these were excluded from the full-length review as they did not report the outcome of interest, while six articles were excluded because they were not observational studies. Thus, 15 studies (10 cohort studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] with a total of 431 KTx recipients and 5 cohort studies [ 68 , 69 , 70 , 71 , 72 ] with a total of 108 living kidney donors) were included. The literature retrieval, review, and selection process are demonstrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, living donor KTx provides greater allograft longevity than those transplanted from a deceased donor [ 57 ]. However, changes in serum klotho levels and the impact of klotho on outcomes among KTx recipients and kidney donors remain unclear [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Thus, we conducted this systematic review and meta-analysis to assess serum klotho levels and the impact of klotho on outcomes among KTx recipients and kidney donors…”
Section: Introductionmentioning
confidence: 99%